Efforts to increase small land productivity through the cultivation of family medicinal plants in order to create a healthy village - Adi Doniarsah; Siti Rodiatun Hopsah; Lisa Lestari; Madiyah Rosilawati; Isah Saputri; Wa Ode Lismawati Sudiri; Nur Aisyah Widiyasari; Diva Devina Dienaqaila; Arief Rahman Hakim; Agung Praayoga Budiargo; Agci Hikmawati (Universitas Muhammadiyah Magelang, 2023)
Pergam Village has a lot of small land that has not been utilized optimally. One solution is to plant family medicinal plants (TOGA). The aim of this community service is to educate partners in utilizing small land as a productive development of TOGA plants towards a healthy village in prevention efforts, increasing health awareness and treatment. The program is carried out with training, mentoring, practice and demonstrations. The result of this program is increased public understanding of the family medicinal plants and increased productivity of small land in Pergam village which contributes to maintaining community immunity from potential diseases in the future.